Ex vivo detection and quantification of apically extruded volatile compounds and disinfection by-products by SIFT-MS, during chemomechanical preparation of infected root canals. Issue 2 (February 2020) - Ioannidis, K; Batty, C; Turner, C; Smith, D; Deb, S; Mannocci, F
Highlights: The application of SIFT-MS has proved an excellent analytical tool to study the formation of VOCs and DBPs. The interaction of 2.5% NaOCl and 17% EDTA resulted in the formation of formaldehyde. The mechanical preparation and irrigation of artificially infected root canals resulted in the formation and apical extrusion of toxic VOCs and DBPs. Further risk assessment of the potential occupational and health hazards should be carried out in dental premises. Abstract: Objectives: To assess the release and apical extrusion of toxic volatile compounds and disinfection by-products during instrumentation and irrigation of artificially infected root canal specimens, with sodium hypochlorite and ethylene diamine tetra acetic acid. Methods: Forty-two single-rooted human teeth were decoronated to obtain 15 mm-long root specimens and working length was determined 1 mm short of root apex. All specimens were initially preflared, to create sufficient conical space for the development of a nutrient-stressed multispecies biofilm. The specimens were randomly assigned into three groups [Group 1; no endodontic intervention, Group 2; instrumentation with rotary files and irrigation with sterile saline, Group 3; instrumentation with rotary files and irrigation with 2.5% sodium hypochlorite (NaOCl) and 17% ethylene diamine tetra acetic acid (EDTA)]. A customised experimental model apparatus was fabricated for each specimen. The apical root third was inserted in a glass vial filled with sterile ultrapure water, to simulate high-compliance periradicular space. The reaction products of the aliquots obtained from the glass vials were analysed in real time, by selected ion flow tube mass spectrometry (SIFT-MS) in triplicates. Two-way analysis of variance (ANOVA) with post hoc Tukey tests were used for data analysis. The level of statistical significance was set at P < 0.05. Results: The group of teeth that were not subjected to endodontic intervention did not show any volatile compounds (VOCs) or disinfection by products (DBPs) whilst instrumentation and irrigation of root canals (Groups 2 and 3) resulted in the apical extrusion of VOCs and DBPs. In Group 3, the aliquots obtained from periradicular space released high concentrations of methanol, propanol, ammonia, chloroform, together with unexpected higher levels of formaldehyde, which were statistically significant compared to Group 2 (P < 0.05). Significance: The mechanical preparation and irrigation of artificially infected root canals with rotary files, 2.5% NaOCl and 17% EDTA resulted in the formation of toxic VOCs and DBPs in a water-closed periradicular space. The chemical interaction of NaOCl and EDTA resulted in the generation of high concentrations of formaldehyde. The formation of chloroform and formaldehyde indicate that risk assessment of the potential hazards to health should be carried out.